The Mobility Turn in the Social Science - Szymanowski, Rafał (My University, 2016)
The paper describes the latest upsurge in the interest in the different forms of mobility in the contemporary world. In the social science this process is often called the mobility turn. In the text it is argued that theoretical underpinnings of the mobility turn are rooted mainly in the different variants of theories of globalization. The text describes: mobility as one of the key elements in the varying concepts of globalization; ways in which mobility was analyzed in the globalization literature; main sources of the mobility turn; crucial arguments in favor of introducing “mobilities” as a separate field of research; and the most important critical remarks concerning the mobility turn.
Keywords: mobilities; mobility turn; social science; globalization theory; global cities; public policy